2014
DOI: 10.3945/ajcn.113.071530
|View full text |Cite
|
Sign up to set email alerts
|

Nuts in the prevention and treatment of metabolic syndrome

Abstract: Nuts are rich in many bioactive compounds that can exert beneficial effects on cardiovascular health. We reviewed the evidence relating nut consumption and the metabolic syndrome (MetS) and its components. Nuts reduce the postprandial glycemic response; however, long-term trials of nuts on insulin resistance and glycemic control in diabetic individuals are inconsistent. Epidemiologic studies have shown that nuts may lower the risk of diabetes incidence in women. Few studies have assessed the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 92 publications
1
24
0
1
Order By: Relevance
“…Therefore, an essential strategy in the clinical management of people at risk of MetS is to place major emphasis on therapeutic lifestyle changes, including diet. Some dietary components have been associated with lower risk of MetS or its components, although their potential beneficial effect in older people is more controversial . It has been proposed that diets with a high glycemic index (GI) and high glycemic load (GL) are associated with greater risks of obesity, T2DM, MetS, and CVD .…”
mentioning
confidence: 99%
“…Therefore, an essential strategy in the clinical management of people at risk of MetS is to place major emphasis on therapeutic lifestyle changes, including diet. Some dietary components have been associated with lower risk of MetS or its components, although their potential beneficial effect in older people is more controversial . It has been proposed that diets with a high glycemic index (GI) and high glycemic load (GL) are associated with greater risks of obesity, T2DM, MetS, and CVD .…”
mentioning
confidence: 99%
“…The research analyzed 11-year incidence of type 2 diabetes, and reported 21% lower risk of diabetes with greater fruits and vegetables intake in diet (Cooper et al, 2012). A research based on epidemiological and clinical trials found that nuts can improve post-prandial glycemia and reduce the risk of diabetes [20]. Many studies have reported the relation between nut consumption and metabolic syndrome (MetS).…”
Section: Plant-based Diet and Diabetesmentioning
confidence: 99%
“…Nuts have been found to play an important role in adjusting the components of MetS by influencing inflammation, oxidative stress, and endothelial function. This in process influences the insulin sensitivity and reduces chances of diabetes, hypertension and obesity [20].…”
Section: Plant-based Diet and Diabetesmentioning
confidence: 99%
“…Consumption of extra virgin olive oil is associated with lower CVD risk and mortality in people with high cardiovascular risk (Guasch-Ferre et al 2014). Eating a diet rich in polyphenols containing olive oil can decrease the BP and improve endothelial function (MorenoLuna et al 2012).…”
Section: Tyrosol and Hydroxytyrosolmentioning
confidence: 99%